Thermal, Chemical, and Photocatalytic Inactivation of Lactobacillus plantarum Bacteriophages - Briggiler Marcó, Mariángeles (2009)
The effect of several biocides, thermal treatments, and photocatalysis on the viability of four Lactobacillus plantarum phages was investigated. Times to achieve 99% inactivation (T₉₉) of phages at 63, 72, and 90 degrees C were evaluated in four suspension media: deMan Rogosa Sharpe broth, reconstituted skim milk, a commercial EM-glucose medium, and Tris magnesium gelatin buffer. The four phages studied were highly resistant to 63 degrees C (T₉₉ > 45 min); however, counts < 10 PFU/ml were achieved by heating at 90 degrees C for 5 min. Higher thermal resistance at 72 degrees C was observed when reconstituted skim milk and EM-glucose medium were assayed. Peracetic acid (0.15%, vol/vol) was an effective biocide for the complete inactivation of all phages studied within 5 min of exposure. Sodium hypochlorite (800 ppm) inactivated the phages completely within 30 min. Ethanol (100%) did not destroy phage particles even after 45 min. Isopropanol did not have any effect on phage viability. Phage counts < 50 PFU/ml were obtained within 180 min of photocatalytic treatment. The results obtained in this work are important for establishing adequate methods for inactivating phages in industrial plants and laboratory environments.